Sociodemographic factors associated with suicide mortality rates in Mexico, 2012-2016 - Dávila-Cervantes, Claudio Alberto (Universidad y Salud, 2019)
Introduction: Mortality due to suicide has increased steadily and continuously in Mexico for more than 40 years. Objective: The main objective was to analyze the sociodemographic factors associated with suicide mortality rates in Mexico between 2012 and 2016. Materials and methods: An observational and cross-sectional study was conducted. Death databases were obtained from the National Institute of Statistics and Geography in Mexico for 2012-2016. A binomial logistic regression model was adjusted to analyze which sociodemographic factors are related to the possibility that people die of suicide in Mexico. Results: Women had a lower chance of dying from suicide, and as age increases, people are less likely to commit suicide. Having some level of schooling or performing an economic activity increased the possibility of death by suicide. Conclusions: This study is expected to provide more evidence to help generate prevention policies, timely care, and the reduction of the impact of suicide on society.